Testing adiabatic models of energetic electron acceleration at dipolarization fronts - Chepuri, S. N. F.; Jaynes, A. N.; Turner, D. L.; Gabrielse, C.; Cohen, I. J.; Baker, D. N.; Mauk, B. H.; Leonard, T.; Blake, J. B.; Fennell, J. F. (Frontiers in Astronomy and Space Sciences, 2023)
Betatron acceleration is commonly cited as a primary accelerator of energetic electrons at dipolarization fronts, and many case studies compare observed energetic electrons measurements to a betatron model. In this work, we extend this to a statistical study. We identified 168 dipolarizations with an enhanced flux of energetic electrons at MMS. We compared the observed flux of energetic electrons above 1 keV to a betatron acceleration model assuming a source population similar to the population in the quiet plasma sheet and found that, on average, the model slightly overestimated the observation, but there was a wide spread of errors. We then tested characteristics such as position, change in and strength of magnetic field, and wave power to determine if any of these characteristics affected the accuracy of the model; the only clear correlations were that the model was less accurate when the initial total magnetic field was smaller and when there was a higher E y during the dipolarization. Since the betatron model did not explain our observations very well, we repeated with a full adiabatic model that included a Fermi acceleration component as well. We found that the adiabatic model slightly underestimated the observations, but with a smaller error than the betatron model under the same assumptions.Testing the same parameters, we found that the adiabatic model also did not strongly rely on any of the parameters except the initial magnetic field, and the anti-correlation with E y was no longer present. The fact that neither model was generally applicable means that either adiabatic processes alone are not enough to explain electron acceleration at dipolarization fronts in general, or the common assumption we used, that the source population has the same phase space density as the cold pre-existing population, is not valid.